A Multimodal Fatigue Detection System Using sEMG and IMU Signals with a Hybrid CNN-LSTM-Attention Model - Hwang, Soree; Kwon, Nayeon; Lee, Dongwon; Kim, Jongman; Yang, Sumin; Youn, Inchan; Moon, Hyuk-June; Sung, Joon-Kyung; Han, Sungmin (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Physical fatigue significantly impacts safety and performance across industrial, athletic, and medical domains, yet its detection remains challenging due to individual variability and limited generalizability of existing methods. This study introduces a multimodal fatigue detection system integrating surface electromyography (sEMG) and inertial measurement unit (IMU) signals, processed through a hybrid convolutional neural network-long short-term memory-attention (CNN-LSTM-Attention) model. Fatigue was induced in 35 healthy participants via step-up-and-down exercises, with gait data collected during natural walking before and after fatigue. The model leverages sEMG from the gastrocnemius lateralis and IMU-derived jerk signals from the tibialis anterior and rectus femoris to classify fatigue states. Evaluated using leave-one-subject-out cross-validation (LOSOCV), the system achieved an accuracy of 87.94% with bilateral EMG signals and a balanced recall of 87.94% for fatigued states using a combined IMU-EMG approach. These results highlight the system's robustness for personalized fatigue monitoring, surpassing traditional subject-dependent methods by addressing inter-individual differences.